Tris(pentafluoroethyl)stannane: Tin Hydride Chemistry with an Electron‐Deficient Stannane. Issue 11 (30th January 2018) - Wiesemann, Markus; Niemann, Mark; Klösener, Johannes; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract: A versatile two‐step synthesis of tris(pentafluoroethyl)stannane, HSn(C2 F5 )3, is presented. Electron‐withdrawing C2 F5 groups significantly influence the polarity of the tin–hydrogen bond, which allows facile deprotonation of the compound, even in water. The utility of this electron‐deficient stannane was illustrated in hydrostannylations of alkenes and alkynes, as well as in dehalogenation reactions. The remarkably high reactivity of HSn(C2 F5 )3 is demonstrated in fast hydrostannylations, even in the absence of activators, whereby the regioselectivity of this process turns out to be solvent dependent. It is of great advantage that in dehalogenation reactions volatile halogenotris(pentafluoroethyl)stannanes, XSn(C2 F5 )3 (X=I, Br), are formed that allow facile separation of the tin‐containing byproducts from the reaction mixtures. Abstract : Volatile separations : A versatile two‐step synthesis of tris(pentafluoroethyl)stannane, HSn(C2 F5 )3, as a rare example of an electron‐deficient stannane is presented. The utility of this volatile stannane is illustrated through the hydrostannylations of alkenes and alkynes, and dehalogenation reactions in the absence of activators.